The influence of the music genre on the emotional consumer response and intentions to purchase online - Vytautas Dikčius; Indrė Radavičienė; Živilė Gerulytė (Trends Economics and Management, 2019)
Purpose of the article: How online shop atmosphere (different background music genre) affects emotional states depending on different product categories; and how the emotional states induced by website atmosphere affect satisfaction with background music, e-shop quality perception and purchase intention responses. Methodology/methods: Experiment, mixed ANOVA and linear regression. Scientific aim: The current study confirmed the stimulus-organism-response relationship by using online stimuli affected the emotion and attitude towards the site (emotional/cognitive states) and consequently influenced purchase intent (response). Findings: The results indicated that the manipulation of different music genres makes it possible to assess whether there are differences between the music genre impact on the emotional response. The impact of different product categories on the emotional response was identified. The analysis results showed that emotional response was positively associated with the intention to buy when popular music was playing as the background of the e-shop; furthermore, the positive impact was identified when the quality factor was operating. Conclusions: It is concluded that the emotional response is positively associated with the intention to buy when popular music is playing, further-more, the positive impact is identified when the quality factor is operating. When no music is playing, the emotional response has a negative impact on the intention to buy. The study limitation can be perceived in the fact that the same respondent evaluated only one of the online stores - it is useful to compare the same respondent's emotional response and intention to buy both utilitarian and hedonistic products in e-shops.
Keywords: M15; M21; 650; music genre; emotional response; purchase intention; online shopping; website quality perception